Creation of Audiovisual Media for Children with Special Needs in Indonesian Language Learning - Ramadania, Fajarika; Kisyani, K; Mintowati, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
This study aims to find out: 1) The influence of learning methods by using audio visual media on the results of learning Bahasa Indonesia. 2) Interaction between learning methods and gender towards the learning outcomes of Indonesian subjects. This research is qualitative research using data collection techniques by conducting interviews and documentation. The informants in this study were teachers and principals. This research also uses literacy method (literature study) by reviewing various literature related to the application of Audio Visual model, Special Needs Children Education (Inclusion Education), and learning media. The data is then analyzed and then presented in the results and discussions in order to be concluded. The results showed that the use of learning methods using media, namely audio visual media has a significant effect on the learning outcomes of Indonesian education in students with needs, especially autism.